2020
DOI: 10.1097/md.0000000000021544
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of noninvasive and invasive acupuncture in preventing postoperative nausea and vomiting

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, the use of preventive antiemetics, an opioid-sparing strategy combined with multimodal analgesia techniques, is also available. [29,30] Overall, the use of strategies to lower the baseline risk of PONV (decreasing water deprivation time, reducing opioid usage, and multimodal analgesia) will reduce the likelihood of patients developing PONV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of preventive antiemetics, an opioid-sparing strategy combined with multimodal analgesia techniques, is also available. [29,30] Overall, the use of strategies to lower the baseline risk of PONV (decreasing water deprivation time, reducing opioid usage, and multimodal analgesia) will reduce the likelihood of patients developing PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers shift their focus on complementary and alternative therapies, and find some of them indeed reduce the incidence of comorbidities. [ 28 ] SAHP, a special acupoint herbal patching mixed acupoint stimulation and time effect, has become a popular therapy to treat AR with prosperity of TCM. Compared to western medicine, SAHP has advantages in safety, low expense, no drug resistance and fewer adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…So the researchers shifted their focus to complementary and alternative therapies, and found that some of them did reduce the incidence of comorbidities. SAHP is a special Chinese medicine acupoint dressing (Fu, C. W., Shu, Q., Jiao, Y., et al, 2020). The combination of acupoint stimulation and time effect has become a popular treatment for AR.…”
Section: Summary and Reflectionmentioning
confidence: 99%